A cross-sectional analysis of snacking habits, eating habits, physical activity, and indicators of obesity among high school students in Jakarta, Indonesia - Intan Lisetyaningrum; Hening Pujasari; Kuntarti Kuntarti (SAGE Publishing, 2021)
Background: Changes in the lifestyle and eating habits of people in large cities in Indonesia have increased the risk of obesity. In Indonesia, the prevalence of obesity in adolescents increased from 1.6% in 2013 to 4.0% in 2018; in Jakarta, it increased from 4.2% in 2013 to 8.3% in 2018. Obesity is closely related to health behavior in adolescence, and it is a risk factor for the occurrence of non-communicable diseases (NCDs). This study aimed to describe the snacking habits, eating habits, physical activity, and indicators of obesity among adolescents in Jakarta.  Design and Methods: This study used a cross-sectional design involving 170, 10th-12th grade public high school students in Jakarta Province, recruited using purposive sampling technique. Using standardized instruments, the following surveys were delivered online: The Beverage and Snack Questionnaire, the Eating Habits Questionnaire, and the Youth Risk Behavior Survey Questionnaire (Q78). The Chi-squared test was used to determine the correlation between the study's variables. Results: The majority of the 170 respondents were female (81.2%). Among the respondents, 11.2% were obese and 6.5% were overweight. Of the 170 respondents 52.4% had the habit of snacking, 64.1% had healthy eating habits, 73.5% engaged in physical activity ≤3 days/week, 79.4% watched TV <3 hours/day, and 61.2% played video games and spent time on computers ≥3 hours/day. The bivariate analysis results showed that there was no significant relationship between snacking habits, eating habits, and physical activity with indicators of obesity (p>0.05). Conclusions: In general, the respondents in our study were found to have a healthy lifestyle, thus helping to prevent the development of an NCD. However, a number of the respondents were overweight and obese.